2002
DOI: 10.1034/j.1600-0412.2002.811208.x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of histopathologic prognostic factors for invasive cervical cancer treated with radical hysterectomy and systematic retroperitoneal lymphadenectomy

Abstract: LN status, parametrial invasion, LVSI, and histology of pure adenocarcinoma are important histopathologic prognostic factors of cervical carcinoma treated with radical hysterectomy and systematic retroperitoneal lymphadenectomy. Prognosis for patients with cervical carcinoma may be stratified by combined analysis of these histopathologic prognostic factors. Postoperative therapy needs to be individualized according to these prognostic factors and validated for its efficacy using randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
109
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(129 citation statements)
references
References 25 publications
(32 reference statements)
15
109
0
5
Order By: Relevance
“…histologic type, histologic grade, tumor size, depth of stromal invasion, LVSI, venous invasion, parametrial involvement, lymph node metastasis, vaginal involvement, or invasive pattern), or ancillary investigation results (i.e. DNA index by flow cytometry or HPV18 detection) (Kamura et al, 1992;Sevin et al, 1996;Lai et al, 1999;Trattner et al, 2001;Takeda et al, 2002;Grisaru et al, 2003;Ayhan et al, 2004;Ho et al, 2004;Shinohara et al, 2004;Lai et al, 2007;Metindir and Bilir, 2007;Sartori et al, 2007;Behtash et al, 2009;Biewenga et al, 2009;2011). When applied to our patient population, only two of these prognostic models by Shinohara et al (2004) and Ho et al (2004) could identify the patient group with a significantly higher recurrence rate than the remaining cases (p<0.05).…”
Section: Prognostic Model In Patients With Early-stage Squamous Cell mentioning
confidence: 99%
“…histologic type, histologic grade, tumor size, depth of stromal invasion, LVSI, venous invasion, parametrial involvement, lymph node metastasis, vaginal involvement, or invasive pattern), or ancillary investigation results (i.e. DNA index by flow cytometry or HPV18 detection) (Kamura et al, 1992;Sevin et al, 1996;Lai et al, 1999;Trattner et al, 2001;Takeda et al, 2002;Grisaru et al, 2003;Ayhan et al, 2004;Ho et al, 2004;Shinohara et al, 2004;Lai et al, 2007;Metindir and Bilir, 2007;Sartori et al, 2007;Behtash et al, 2009;Biewenga et al, 2009;2011). When applied to our patient population, only two of these prognostic models by Shinohara et al (2004) and Ho et al (2004) could identify the patient group with a significantly higher recurrence rate than the remaining cases (p<0.05).…”
Section: Prognostic Model In Patients With Early-stage Squamous Cell mentioning
confidence: 99%
“…A US study of patients from 1997 to 2003 in the SEER database found 5-year overall survivals of 32.5% for patients with SNEC, 74.3% for ADC and 64.6% for SCC (Chen et al, 2008). Some studies have reported 2.6-2.9 times higher mortality among patients with early stage ADC compared with early-stage SCC patients over 10-19 years of follow-up (Nakanishi et al, 2000;Takeda et al, 2002;Park et al, 2010;Mabuchi et al, 2012) while others have not found any significant difference in survival among patients with SCC and ADC (Shingleton et al, 1995;Lee et al, 2006;Fregnani et al, 2008;Kasamatsu et al, 2009;Narukon et al, 2010). Moreover, only few studies have included patients with SNEC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that histological type is an important prognostic factor (Nakanishi et al, 2000;Takeda et al, 2002;Vinh-Hung et al, 2007;Chen et al, 2008;Zivanovic et al, 2009;Lee et al, 2010;Park et al, 2010). A US study of patients from 1997 to 2003 in the SEER database found 5-year overall survivals of 32.5% for patients with SNEC, 74.3% for ADC and 64.6% for SCC (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The most important and widely studied prognostic variables for cervical cancer are lymph node spread, tumor size, involvement of parametrial tissue, depth of invasion, and lymphovascular invasion. [3][4][5][6] The incidence of patients with lymph node involvement increased with parametrial extension (P < .01). The corrected 5-year survival rates were 94% for patients with stage IB disease, 95% for patients with stage IIA disease, and 78% for patients with stage IIB disease.…”
mentioning
confidence: 99%
“…4 Similarly, it was reported that lymph node status, parametrial invasion, lymphovascular space invasion, and a histology of pure adenocarcinoma were important histopathologic prognostic factors for patients with early-stage cervical carcinoma who underwent radical surgery. 5 Although lymphovascular invasion does not alter FIGO staging, if the lymphovascular invasion is >3 mm and < 5 mm, then the risk of recurrence is 15.7% compared with a risk of only 3.1% if the invasion is < 3 mm. 6 Positron emission tomography (PET) is an in vivo, functional imaging modality that depends on the metabolic behavior of the viable cells.…”
mentioning
confidence: 99%